An Excel Based Tool Development for Scheduling Optimization - Muhammad Afwan Mohamad; Zulfan Adi Putra; M Roil Bilad; Nik Abdul Hadi Md Nordin; M Dzul Hakim Wirzal (ASEAN Journal of Science and Engineering Education, 2021)
Scheduling can be seen in many areas such as chemical processing, logistic, supply chain, and class. In this study, two different cases of scheduling problems are addressed which are batch reactor process scheduling and University Class Scheduling (UCS) problems. The aim for the batch reactor process scheduling is to minimize the total discrepancies between the size of the assigned reactors and their corresponding assigned capacities or reactor sizes. The approach taken into consideration includes some constraints such as desired products, the production capacities, and the reactor capacities. Meanwhile, for the UCS problem, the concern is on the number of needed courses assign to certain classrooms while at the same time noting the constraints such as the size of the classroom and the number students. The UCS problem also seeks to optimize the distribution of courses remarkably to classrooms refers to the ratio of classroom capacity to course enrolment. These issues will be resolved using Integer Linear Programming (ILP) in the form of Excel-based software. The ILP model tool for both scheduling problems, therefore, is developed and resolved using the Excel solver utilizing Visual Basic Applications (VBA) and Macro.